Productive Zakat and Women's Empowerment for Inclusive Economy: Sharia Economic Law And Social Fiqh in Indonesia - Saadah, Chuzaimatus; Salsabila, Az Zahra Aulya; Khalimah, Dwi (Institut Agama Islam Negeri Metro, 2024)
Women significantly contribute to the national economy through their Micro, Small, and Medium Enterprises (MSMEs) roles. However, they face inadequate support from government and private sectors in accessing formal financial services. This research addresses the gap in gender-inclusive financial support by exploring the potential of productive Zakat within the framework of Sharia Economic Law in Indonesia and social fiqh. The study aims to evaluate how productive Zakat can mitigate gender inequality and promote economic inclusion for women. A qualitative methodology with a normative approach was employed to address this issue, utilizing the social fiqh paradigm for analysis. As a legal product, the findings reveal that fiqh evolves with societal changes. Social realities, such as the discrimination women face in accessing financial resources, necessitate the adaptive allocation of Zakat. Precisely, dedicating Zakat to women reflects their unique economic challenges and highlights the need for specialized management structures to distribute productive Zakat effectively. This study contributes to the existing literature by demonstrating the practical application of Sharia Economic Law in Indonesia and social fiqh in addressing contemporary gender disparities in economic participation. The novelty lies in proposing a structured and professional management system for productive Zakat to empower women, fostering economic inclusivity.